Promosi Kesehatan dengan Film Cerita Pendek tentang Aktivitas Fisik pada Anak Usia Sekolah di Panti Asuhan Ummi Ikhlas Kota Jambi - Razi, Pahrur; Iksarudin, Iksarudin; Surayah, Surayah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The most common causes of death in Indonesia are non-communicable diseases such as stroke, chronic kidney disease, diabetes mellitus, and hypertension. Lack of physical activity will have the potential to cause non-communicable diseases. Intensive health education efforts are needed with various innovative uses of IT to improve PHBS, especially physical activity such as through short story films. This PKM aims to increase perceptions and motivation to do physical activity and test the effectiveness of community service interventions through health promotion with short story films about physical activity. The implementation method is to carry out pre and post-tests through data collection from primary data obtained from questionnaires and observation formats. This PKM will be carried out in May-June 2023 with 80 participants at the Ummi Ikhlas Jambi Orphanage, involving students in data collection. The results increased the perception and motivation to carry out physical activity in school-age children at the Ummi Ikhlas Orphanage, Jambi City, from 25% (pretest) to 100% (posttest). It is recommended to increase it regularly to 2 times a week every morning on Wednesdays and Fridays, doing gymnastics at the Ummi Ikhlas Jambi Orphanage.